(untitled) (International Journal of Engineering and Computer Science, 2018)
In this optional method, controlled current source CCS with controlled voltage source CVS is used to increase the high power system station acts. The traditional system causes high odd and even harmonics for current and voltage that it leads to decreasing the system efficiency. The output sinewave voltage and current is distorted with more unstable. Therefore, the best solution for this critical situation, CCS with CVS controller are used to develop the efficiency by reducing the steady state error, decreasing the overshoot with undershoots for system. The results are completed depending on Matlab Simulink with toolbox. The system with two controllers has the consultant over conventional system with increase the active power and minimizing losses power by limitation the harmonics